Neo-Aristotelian Metaphysics and the Theology of Nature - Simpson, William M. R.; Koons, Robert C.; Orr, James (Routledge Studies in Metaphysics, 2022)
Philosophy, metaphysics, philosophy of religion, philosophy of mind, philosophy of science, religion and philosophy, religion and science, christian theology